Aqueous zinc ion battery positive electrode material and preparation method and application thereof

MoS(2-x)Sex@N-C composite material was prepared by electrospinning technology, combining Se elements to expand layer spacing and introduce defects, and using N-doped C-layer to improve conductivity, solving the zinc storage capacity of the positive electrode material of the aqueous zinc ion battery and poor cycle stability, higher zinc storage performance is achieved.

CN119160943APending Publication Date: 2024-12-20XIAN AERONAUTICAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411340122.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing positive electrode materials of the current aqueous zinc ion battery have low zinc storage capacity and poor circulation stability due to slow zinc storage kinetics and poor conductivity.

Method used

The MoS(2-x)Sex@N-C composite material was prepared by electrospinning technology, and the layer spacing was expanded and defects were introduced by introducing Se elements, and the conductivity was improved by combining the N-doped C-layer to achieve a comprehensive strategy of layer spacing expansion and defect engineering.

Benefits of technology

The zinc storage capacity and cycle stability of the positive electrode material of zinc ion battery are significantly improved, and the problem of poor conductivity is solved, and the zinc storage performance is higher.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160943A_ABST
    Figure CN119160943A_ABST
Patent Text Reader

Abstract

The invention discloses an aqueous zinc ion battery positive electrode material and a preparation method and application thereof. The invention particularly relates to a MoS (2-x) Se < x > (at) N-C composite material prepared by an electrostatic spinning technology. The preparation method comprises the following steps: firstly, preparing an electrostatic spinning solution containing a molybdenum source (such as ammonium molybdate or ammonium tetrathiomolybdate), a sulfur source (such as thioacetamide or thiourea) and a selenium source (such as Se powder or SeO2), and preparing a composite prefabricated film containing precursors of the three elements through an electrostatic spinning method; and then, carrying out two-stage calcination treatment on the prefabricated film under set conditions to form the final MoS (2-x) Se < x > (at) N-C composite material. According to the MoS (2-x) Se < x > (at) N-C composite positive electrode material prepared by the invention, interlayer defects are introduced while the interlayer spacing of the material is expanded, so that the zinc storage capacity, the cycling stability and the electrochemical performance of the aqueous zinc ion battery are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aqueous zinc ion batteries, and in particular relates to an aqueous zinc ion battery positive electrode material and a preparation method and application thereof. Background Art

[0002] Aqueous zinc-ion batteries (ZIBs) are expected to become one of the most promising energy storage systems for the next generation due to their high safety, low cost, and environmental friendliness. As a key component of batteries, the structural design and optimization of cathode materials play a crucial role in the development of high-performance aqueous ZIBs.

[0003] The cathode materials that are currently being widely studied mainly include manganese-based, vanadium-based, and molybdenum-based oxides and sulfides. Molybdenum disulfide (MoS2) has attracted the attention of researchers due to its unique two-dimensional layered crystal structure. The layers are connected by weak van der Waals forces, which facilitates the insertion of guest ions into the interlayers. In aqueous ZIBs batteries, Zn 2+ The high desolvation and intercalation barriers make the reaction kinetics in the host material slow, resulting in Zn 2+ Reversible deintercalation in MoS2 is difficult. 2+ Indicators such as interlayer spacing and conductivity, which are closely related to diffusion dynamics, determine the zinc storage performance of MoS2.

[0004] However, the modification strategies for MoS2 in existing research are mainly interlayer spacing expansion or defect engineering. 2+ The fast deintercalation in the MoS2 host provides a channel for the defect-rich MoS 2-x Positive electrode allows Zn 2+ It preferentially embeds into edge sites and sulfur vacancies, and can obtain higher capacity compared with defect-free MoS2. Recently, some researchers have successfully expanded the interlayer spacing of MoS2 by using guest species intercalation or heteroatom doping. For example, Li Shengwei et al. embedded graphene into the interlayer of MoS2 for the first time, expanding its interlayer spacing from 0.62 nm to 1.16 nm; Husam N. Alshareef's team reported a MoS2 material containing lattice oxygen (MoS2-O), with the interlayer spacing expanded to 0.95 nm; Zhi Chunyi's team prepared a MoS2 nanosheet material grown vertically on a carbon cloth substrate, with the interlayer spacing expanded to 0.70 nm; Wang and his colleagues prepared a defect-rich MoS2 nanosheet, and the presence of defects makes the MoS2 nanosheet have good electrochemical properties. This type of MoS2 with large interlayer spacing or defects shows high Zn 2+ However, there are few reports on MoS2 preparation methods that can expand the MoS2 interlayer spacing and introduce defects at the same time. Summary of the Invention

[0005] The purpose of the embodiments of the present invention is to provide an aqueous zinc ion battery positive electrode material, which can realize the introduction of interlayer defects while expanding the material interlayer spacing, so as to solve the problems of low zinc storage capacity and poor cycle stability caused by slow zinc storage kinetics and poor conductivity of existing positive electrode materials; Another object of the present invention is to provide a method for preparing a positive electrode material for an aqueous zinc ion battery. The third purpose of the embodiment of the present invention is to provide an application of an aqueous zinc ion battery positive electrode material.

[0006] To solve the above technical problems, the technical solution adopted by the present invention is a method for preparing a positive electrode material for an aqueous zinc ion battery, comprising the following steps: An electrospinning solution containing a molybdenum source, a sulfur source, and a selenium source is prepared, and a composite prefabricated membrane containing precursors of the three elements of molybdenum, sulfur, and selenium is prepared by electrospinning; The composite prefabricated membrane is calcined to obtain MoS (2-x) Se x @NC Composites.

[0007] Furthermore, the electrospinning solution containing the molybdenum source, the sulfur source and the selenium source is prepared as follows: A molybdenum source and a sulfur source are added as solutes to N,N-dimethylformamide and stirred until dissolved; anhydrous ethanol and a polymer are then added and stirred until the polymer is dissolved to obtain a DMF mixed solution; a selenium source is then added to a reducing solvent, stirred for 0.5 to 2 hours, and then added dropwise to the DMF mixed solution and stirred at a speed of 300 to 1000 r for 4 to 24 hours to obtain an electrospinning solution containing the molybdenum source, the sulfur source, and the selenium source.

[0008] Furthermore, the molybdenum source includes one or a mixture of ammonium molybdate and ammonium tetrathiomolybdate; the sulfur source includes a mixture of one or more of thioacetamide, thiourea, and sulfur powder; the selenium source includes one of Se powder and SeO2; the polymer is one of polyvinyl pyrrolidone and polyacrylonitrile; when ammonium tetrathiomolybdate is used as the molybdenum source, the sulfur source is not introduced.

[0009] Furthermore, the reducing solvent includes one of hydrazine hydrate and ethylenediamine, and the mass fraction of the reducing solvent is 50% to 80%.

[0010] Furthermore, in the process of adding the molybdenum source and the sulfur source as solutes into N,N-dimethylformamide, the amount and volume ratio of the solute to the solvent is 0.25 to 30 mol / L; In the process of adding anhydrous ethanol and the polymer and stirring until the polymer is dissolved, the mass volume ratio of anhydrous ethanol to the above-mentioned N,N-dimethylformamide is 1.0-2.5 g / mL, and the mass volume ratio of the polymer to N,N-dimethylformamide is 0.5-0.75 g / mL; In the process of adding the selenium source into the reducing solvent and stirring, the amount-to-volume ratio of the selenium source to the reducing solvent is 0.33-30 mol / L.

[0011] Furthermore, in the electrospinning solution containing a molybdenum source, a sulfur source and a selenium source, the molar ratio of the molybdenum source, the sulfur source and the selenium source is 1:2~5:1, the mass fraction of the polymer is 10%~15%, and the molecular weight of the polymer is ≥1300000.

[0012] Furthermore, the electrospinning process is as follows: S201. Allow the electrospinning solution containing the molybdenum source, sulfur source, and selenium source to stand until the spinning solution is uniform and free of bubbles. Then, inject the solution into a 5-20 ml syringe equipped with an 18-25 gauge needle. Connect the needle of the syringe to a 20-40 kV high-voltage power supply. The distance between the needle and the collecting metal plate is 8-12 cm. Set the spinning solution flow rate to 0.5-2.0 ml·h -1 , the spinning time is 4~8h, and the fiber membrane is collected by tin foil; S202. After spinning, the fiber membrane is placed in an oven at a temperature of 40-60°C for drying for 8-12 hours to obtain a uniformly dried composite prefabricated membrane containing the three element precursors of molybdenum, sulfur and selenium.

[0013] Furthermore, the specific process of calcining the composite prefabricated film is as follows: placing the composite prefabricated film containing three elemental precursors of molybdenum, sulfur and selenium into a clean porcelain boat to ensure that the film is fluffy and distributed, and then placing the porcelain boat in a vacuum tube furnace filled with nitrogen; using gradient insulation, setting the heating rate of the first section to 3~10℃ / min, the reaction temperature to 300~500℃, and the insulation time to 60~120min; setting the heating rate of the second section to 3~10℃ / min, the reaction temperature to 600~900℃, and the insulation time to 30~60min, to form MoS (2-x) Se x @NC Composites.

[0014] The aqueous zinc ion battery positive electrode material is prepared by the above-mentioned aqueous zinc ion battery positive electrode material preparation method.

[0015] As for the application of the positive electrode material of the aqueous zinc ion battery mentioned above, the positive electrode material is applied to the aqueous zinc ion battery.

[0016] Compared with the prior art, the present invention has the following advantages: (1) The present invention constructs N-doped C-coated MoS with controllable composition (2-x) Se x Composite cathode structure, by introducing Se element to replace part of S element in MoS2, on the one hand, the radius of Se is larger than S to expand the interlayer spacing of MoS2, on the other hand, Se replaces S in situ to distort the MoS2 lattice and generate defects inside MoS2 at the same time, and the doping amount of Se is used to control the MoS (2-x) Se x The composition and defect concentration of MoS (2-x) Se x The outer N-doped C layer improves the conductivity of the positive electrode. This method can simultaneously improve the zinc storage performance of molybdenum sulfide by combining three strategies: MoS2 layer expansion technology, defect engineering, and conductivity improvement.

[0017] (2) The present invention uses electrospinning technology for the first time to simultaneously inject Mo, S and Se sources into the fiber membrane in the form of ions, and then controls the reaction process through a two-step calcination process. In the low-temperature calcination stage, the Mo and S sources are ensured to fully react to form MoS2, and the initial carbonization and nitrogen doping (NC) of the polymer are completed; in the high-temperature calcination stage, the Se source is able to partially replace the S atoms in MoS2, while increasing the degree of carbonization of the polymer to form MoS (2-x) Se x @NC composite material. The MoS (2-x) Se x @NC composite material as the positive electrode of aqueous zinc-ion batteries exhibits high zinc storage capacity and good cycle stability, solving the problem of poor electrochemical performance of existing molybdenum sulfide positive electrodes and has significant scientific significance in the application of electrode materials in aqueous zinc-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0019] Figure 1 This is a scanning electron microscope photograph of the fiber membrane prepared by electrospinning technology in Example 3 of the present invention.

[0020] Figure 2 The MoS prepared in Example 3 of the present invention (2-x) Se x @Scanning electron microscope image of NC composite material.

[0021] Figure 3The MoS prepared in Example 3 of the present invention (2-x) Se x @X-ray diffraction spectrum of NC composite material.

[0022] Figure 4 The MoS prepared in Example 3 of the present invention (2-x) Se x N1s narrow spectrum in the X-ray photoelectron spectrum of @NC composite materials.

[0023] Figure 5 The MoS prepared in Example 3 of the present invention (2-x) Se x @Cycling performance curve of NC composite material.

[0024] Figure 6 This is a scanning electron microscope photograph of the fiber membrane prepared by electrospinning technology in Comparative Example 1.

[0025] Figure 7 This is a scanning electron microscope photograph of the fiber membrane prepared by electrospinning technology in Comparative Example 2. DETAILED DESCRIPTION

[0026] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0027] This embodiment provides a positive electrode material for an aqueous zinc ion battery, specifically a MoS (2-x) Se x @NC material is prepared by the following steps: S1. Prepare electrospinning solution containing Mo source, S source and Se source: S101. Measure 1-4 mL of N,N-dimethylformamide (DMF) and pour it into a small beaker. Then weigh 0.001-0.03 mol of Mo source and S source and pour them into DMF and stir until they are dissolved (the molar volume ratio of solute to solvent is 0.25-30 mol / L). The Mo source here is a nitrogen-containing substance such as ammonium molybdate, ammonium tetrathiomolybdate, or a mixture thereof. The S source is thioacetamide, thiourea, sulfur powder, or a mixture thereof. If a substance including ammonium tetrathiomolybdate is used as the Mo source, the S source is not necessary.

[0028] S102. Add 1.0-10.0 g of anhydrous ethanol and 0.5-3.0 g of a polymer such as polyvinylpyrrolidone (PVP) or polyacrylonitrile (PAN) to the above solution (the mass-to-volume ratio of anhydrous ethanol to the above DMF is 1.0-2.5 g / mL, and the mass-to-volume ratio of the polymer to DMF is 0.5-0.75 g / mL). Stir for 0.5-2 h until the polymer is dissolved.

[0029] S103. Weigh 0.001–0.03 mol of a Se source, such as Se powder or SeO₂, and add it to 1–3 mL of a reducing solvent (Se source and reducing solvent: 0.33–30 mol / L). The reducing solvent should consist of 50%–80% by mass of hydrazine hydrate or ethylenediamine. Premix and dissolve the Se source and reducing solvent (hydrazine hydrate, ethylenediamine, etc.) to ensure the Se is in the proper form, which facilitates its effective binding to the Mo-S precursor. Stir for 0.5–2 h and then add the Se source dropwise to the mixed solution. Adding the Se source dropwise helps form a more uniform mixture; adding the Mo and Se sources separately avoids this. The molar ratio of the Mo, S, and Se sources in the mixed solution should be 1:2–5:1. The mass fraction of the polymer should be 10%–15%, and the molecular weight of the polymer should be greater than or equal to 1,300,000. Stir the mixed solution for 4–24 h at a speed of 300–1,000 rpm.

[0030] S2. Prepare a prefabricated membrane containing Mo source, S source and Se source precursors by electrospinning: Introducing molybdenum (Mo), sulfur (S), and selenium (Se) sources into the fiber membrane in ionic form allows for uniform dispersion of the raw materials within the fiber structure. During subsequent heat treatment, these ions react in situ to form corresponding compounds while maintaining their uniform distribution, preventing agglomeration of active sites.

[0031] S201. After the spinning solution is allowed to stand until it is uniform and free of bubbles, the mixed solution is injected into a 5-20 ml plastic syringe equipped with an 18-25 gauge needle. The needle of the syringe is connected to a 20-40 kV high-voltage power supply. The distance between the needle and the collecting metal plate is 8-12 cm. The spinning solution flow rate is set to 0.5-2.0 ml·h -1 , the spinning time was 4-8 h, and the fiber membrane was collected by tin foil; S202, after the spinning is completed, the fiber membrane is placed in an oven at a temperature of 40-60° C. and dried for 8-12 hours to obtain a uniformly dried composite prefabricated membrane containing precursors of the three elements of molybdenum, sulfur and selenium; S3, calcining the prefabricated film to prepare MoS (2-x) Se x @NC Composites: S301. Remove the film from the surface of the tin foil with tweezers and place it in a clean porcelain boat, ensuring that the film is fluffy and distributed. Then place the porcelain boat in a vacuum tube furnace filled with nitrogen. Use gradient insulation. Set the heating rate of the first stage to 3~10℃ / min, the reaction temperature to 300~500℃, and the insulation time to 60~120min. This allows the Mo source and the S source to react fully to form MoS2, and complete the initial carbonization of the polymer and the doping of nitrogen elements. Set the heating rate of the second stage to 3~10℃ / min, the reaction temperature to 600~900℃, and the insulation time to 30~60min. This allows the Se source to partially replace the S atoms in MoS2, while increasing the degree of carbonization of the polymer to form MoS (2-x) Se x @NC Composites.

[0032] S302, after the reaction is completed in a nitrogen atmosphere, the sample is collected to obtain N-doped C-coated MoS (2-x) Se x (MoS (2-x) Se x @NC) composite cathode material. This embodiment partially replaces the S element in MoS2 by introducing Se element, not only using the larger radius of Se atoms (the atomic radius of Se is 1.17 Å, while the atomic radius of S is 1.02 Å) to effectively expand the interlayer spacing of the MoS2 layered structure, thereby improving its ion diffusion channel; but also through the in-situ replacement of S by Se, the MoS2 lattice is distorted, and abundant defect sites are introduced into the material. These defects help to promote the number of active sites, thereby improving the kinetics of the electrochemical reaction. By precisely controlling the doping amount of Se, not only can the MoS (2-x) Se x The chemical composition of MoS can also be controlled to regulate the concentration of its internal defects, which is crucial for optimizing the electrochemical performance of the material. (2-x) Se x The core is coated with a nitrogen-doped carbon layer, which not only improves the electron conductivity of the cathode material, but also further enhances the chemical stability and electrochemical activity of the material surface. This embodiment integrates multiple strategies of MoS2 interlayer spacing expansion technology, lattice defect engineering, and conductivity enhancement to synergistically enhance the zinc storage performance of MoS2 as a cathode material for aqueous zinc-ion batteries, giving it higher zinc storage capacity and better cycling stability.

[0033] Example 1 MoS for positive electrode of aqueous zinc ion battery (2-x) Se x @NC material and preparation method thereof, comprising the following steps: S1. Prepare electrospinning solution containing Mo source, S source and Se source: S101. Pour 1 mL of N,N-dimethylformamide (DMF) into a small beaker. Then weigh 0.001 mol of ammonium molybdate and 0.002 mol of thioacetamide, add them to the DMF, and stir until dissolved.

[0034] S102. Add 1.0 g of anhydrous ethanol and 0.5 g of polyvinylpyrrolidone (PVP) to the above solution and stir for 0.5 h until the PVP is dissolved.

[0035] S103. Weigh 0.001 mol of Se powder and add it to 1 mL of 50% hydrazine hydrate. Stir for 0.5 h, then add it dropwise to the mixed solution. The molar ratio of Mo, S, and Se sources in the mixed solution is 1:2:1, and the mass fraction of the polymer is 12.7%. Stir the mixed solution for 4 h at 300 rpm.

[0036] S2: Preparation of a prefabricated membrane containing Mo, S and Se sources by electrospinning: S201: After the spinning solution is allowed to stand until it is uniform and free of bubbles, the mixed solution is injected into a 5 ml plastic syringe equipped with a 25-gauge needle. The needle of the syringe is connected to a 20 kV high-voltage power supply. The distance between the needle and the collecting metal plate is 8 cm. The spinning solution flow rate is set to 0.5 ml h -1 , the spinning time was 6 h, and the fiber membrane was collected by tin foil; S202: After spinning, the fiber membrane is placed in an oven at 40°C and dried for 8 hours to obtain a uniformly dried prefabricated membrane; S3: calcining the prefabricated membrane to prepare MoS (2-x) Se x @NC Composites: S301: Remove the film from the tin foil surface with tweezers and place it in a clean porcelain boat, ensuring that the film is fluffy and distributed. Then place the porcelain boat in a vacuum tube furnace filled with nitrogen. Use gradient insulation. The first stage is set at a heating rate of 5℃ / min, a reaction temperature of 500℃, and a holding time of 90 minutes. This allows the Mo source and the S source to react fully to form MoS2 and complete the initial carbonization of the polymer. The second stage is set at a heating rate of 10℃ / min, a reaction temperature of 800℃, and a holding time of 30 minutes. This allows the Se source to partially replace the S atoms in MoS2, while increasing the degree of carbonization of the polymer to form MoS (2-x) Se x @C composite materials.

[0037] S302: After the reaction is completed in a nitrogen atmosphere, the sample is collected to obtain N-doped C-coated MoS (2-x) Se x (MoS(2-x) Se x @NC) composite positive electrode materials.

[0038] Example 2 MoS for positive electrode of aqueous zinc ion battery (2-x) Se x @NC material and preparation method thereof, comprising the following steps: S1. Prepare electrospinning solution containing Mo source, S source and Se source: S101. Pour 2 mL of N,N-dimethylformamide (DMF) into a small beaker. Then weigh 0.0015 mol of a mixture of ammonium tetrathiomolybdate and ammonium molybdate (molar ratio of 1:1) into the DMF and stir until dissolved.

[0039] S102. Add 2.0 g of anhydrous ethanol and 1.0 g of polyvinylpyrrolidone (PVP) to the above solution and stir for 1.5 h until the PVP is dissolved.

[0040] S103. Weigh 0.0015 mol of Se powder and add it to 1.5 mL of 60% hydrazine hydrate. Stir for 1.5 hours, then add it dropwise to the mixed solution. The molar ratio of the Mo source, S source, and Se source in the mixed solution is 1:4:1, and the mass fraction of the polymer is 14.3%. Stir the mixed solution for a total of 8 hours at 500 rpm.

[0041] S2: Preparation of a prefabricated membrane containing Mo, S and Se sources by electrospinning: S201: After the spinning solution is allowed to stand until it is uniform and free of bubbles, the mixed solution is injected into a 5 ml plastic syringe equipped with a 24-gauge needle. The needle of the syringe is connected to a 30 kV high-voltage power supply. The distance between the needle and the collecting metal plate is 8 cm. The spinning solution flow rate is set to 0.8 ml h -1 , the spinning time was 4 h, and the fiber membrane was collected by tin foil; S202: After spinning, the fiber membrane is placed in an oven at 50°C and dried for 10 hours to obtain a uniformly dried prefabricated membrane; S3: calcining the prefabricated membrane to prepare MoS (2-x) Se x @NC Composites: S301: Remove the film from the tin foil with tweezers and place it in a clean porcelain boat, ensuring that the film is fluffy and distributed. Then place the porcelain boat in a vacuum tube furnace filled with nitrogen. Use gradient insulation. The first stage is set at a heating rate of 5 ℃ / min, a reaction temperature of 300 ℃, and a holding time of 120 min. This allows the Mo source and the S source to react fully to form MoS2 and complete the initial carbonization of the polymer. The second stage is set at a heating rate of 5 ℃ / min, a reaction temperature of 600 ℃, and a holding time of 30 min. This allows the Se source to partially replace the S atoms in MoS2, while increasing the degree of carbonization of the polymer to form MoS (2-x) Se x @C composite materials.

[0042] S302: After the reaction is completed in a nitrogen atmosphere, the sample is collected to obtain N-doped C-coated MoS (2-x) Se x (MoS (2-x) Se x @NC) composite positive electrode materials.

[0043] Example 3 MoS for positive electrode of aqueous zinc ion battery (2-x) Se x @NC material and preparation method thereof, comprising the following steps: S1. Prepare electrospinning solution containing Mo source, S source and Se source: S101. Pour 2 mL of N,N-dimethylformamide (DMF) into a small beaker. Then weigh 0.0015 mol of ammonium tetrathiomolybdate into the DMF and stir until dissolved.

[0044] S102. Add 2.0 g of anhydrous ethanol and 1.0 g of polyvinylpyrrolidone (PVP) to the above solution and stir for 1.5 h until the PVP is dissolved.

[0045] S103. Weigh 0.0015 mol of Se powder and add it to 1.5 mL of 80% hydrazine hydrate. Stir for 1.5 hours, then add it dropwise to the mixed solution. The molar ratio of the Mo source, S source, and Se source in the mixed solution is 1:4:1, and the mass fraction of the polymer is 14.3%. Stir the mixed solution for a total of 8 hours at 500 rpm.

[0046] S2: Preparation of a prefabricated membrane containing Mo, S and Se sources by electrospinning: S201: After the spinning solution is allowed to stand until it is uniform and free of bubbles, the mixed solution is injected into a 5 ml plastic syringe equipped with a 24-gauge needle. The needle of the syringe is connected to a 40 kV high-voltage power supply. The distance between the needle and the collecting metal plate is 8 cm. The spinning solution flow rate is set to 0.8 ml·h-1 , the spinning time was 4 h, and the fiber membrane was collected by tin foil; S202: After spinning, the fiber membrane is placed in an oven at 50°C and dried for 10 hours to obtain a uniformly dried prefabricated membrane; S3: calcining the prefabricated membrane to prepare MoS (2-x) Se x @NC Composites: S301: Remove the film from the tin foil with tweezers and place it in a clean porcelain boat, ensuring that the film is fluffy and distributed. Then place the porcelain boat in a vacuum tube furnace filled with nitrogen. Use gradient insulation. The first stage is set at a heating rate of 5 ℃ / min, a reaction temperature of 300 ℃, and a holding time of 120 min. This allows the Mo source and the S source to react fully to form MoS2 and complete the initial carbonization of the polymer. The second stage is set at a heating rate of 5 ℃ / min, a reaction temperature of 600 ℃, and a holding time of 30 min. This allows the Se source to partially replace the S atoms in MoS2, while increasing the degree of carbonization of the polymer to form MoS (2-x) Se x @C composite materials.

[0047] S302: After the reaction is completed in a nitrogen atmosphere, the sample is collected to obtain N-doped C-coated MoS (2-x) Se x (MoS (2-x) Se x @NC) composite positive electrode materials.

[0048] like Figure 1 As shown in Figure 2, the morphology of the prefabricated membrane injected with Mo source, S source and Se source was observed using a field emission scanning electron microscope model S4800. The fiber membrane showed a uniformly distributed one-dimensional fiber structure with an average diameter of 2 μm. The structure of the prefabricated membrane after two-step calcination was as shown in Figure 2. Figure 2 As shown in the figure, the overall fiber structure is well preserved; the MoS prepared in this embodiment was analyzed using a Japanese Rigaku Ultima IV X-ray diffractometer. (2-x) Se x @NC composite powder, such as Figure 3 and Figure 4 As shown, the sample is MoS with JCPDS number 36-1410 0.5 Se 1.5 and MoS numbered 36-1409 1.5 Se 0.5 Correspondingly, a diffraction peak of carbon was observed and the nitrogen content was confirmed to be 2.61%. Figure 5 This is the cycling performance diagram of the sample prepared in Example 3 when used as the positive electrode of aqueous ZIBs. The test current density is 100 mA·g -1After 100 cycles, the capacity remains at 185.4 mAh·g -1 .

[0049] Example 4 MoS for positive electrode of aqueous zinc ion battery (2-x) Se x @NC material and preparation method thereof, comprising the following steps: S1. Prepare electrospinning solution containing Mo source, S source and Se source: S101. Pour 3 mL of N,N-dimethylformamide (DMF) into a small beaker. Then weigh 0.008 mol of ammonium molybdate and 0.024 mol of sulfur powder into the DMF and stir until dissolved.

[0050] S102. Add 5.0 g of anhydrous ethanol and 2.5 g of polyacrylonitrile (PAN) to the above solution and stir for 2 h until PAN is dissolved.

[0051] S103. Weigh 0.008 mol of SeO2 into 3 mL of 70% ethylenediamine, stir for 1 hour, and then add dropwise to the above mixed solution. The molar ratio of the Mo source, S source, and Se source in the mixed solution is 1:3:1, and the mass fraction of the polymer is 15%. Stir the mixed solution for a total of 12 hours at 700 rpm.

[0052] S2: Preparation of a prefabricated membrane containing Mo, S and Se sources by electrospinning: S201: After the spinning solution is allowed to stand until it is uniform and free of bubbles, the mixed solution is injected into a 10 ml plastic syringe equipped with a 22-gauge needle. The needle of the syringe is connected to a 30 kV high-voltage power supply. The distance between the needle and the collecting metal plate is 10 cm. The spinning solution flow rate is set to 1.0 ml·h -1 , the spinning time was 8 h, and the fiber membrane was collected by tin foil; S202: After the spinning is completed, the fiber membrane is placed in an oven at a temperature of 60°C and dried for 10 hours to obtain a uniformly dried prefabricated membrane; S3: calcining the prefabricated membrane to prepare MoS (2-x) Se x @NC Composites: S301: Remove the film from the tin foil surface with tweezers and place it in a clean porcelain boat, ensuring that the film is fluffy and distributed. Then place the porcelain boat in a vacuum tube furnace filled with nitrogen. Use gradient insulation. The first stage is set at a heating rate of 3 ℃ / min, a reaction temperature of 400 ℃, and a holding time of 60 min. This allows the Mo source and the S source to react fully to form MoS2 and complete the initial carbonization of the polymer. The second stage is set at a heating rate of 3 ℃ / min, a reaction temperature of 700 ℃, and a holding time of 50 min. This allows the Se source to partially replace the S atoms in MoS2, while increasing the degree of carbonization of the polymer to form MoS (2-x) Se x @C composite materials.

[0053] S302: After the reaction is completed in a nitrogen atmosphere, the sample is collected to obtain N-doped C-coated MoS (2-x) Se x (MoS (2-x) Se x @NC) composite positive electrode materials.

[0054] Example 5 MoS for positive electrode of aqueous zinc ion battery (2-x) Se x @NC material and preparation method thereof, comprising the following steps: S1. Prepare electrospinning solution containing Mo source, S source and Se source: S101. Pour 4 mL of N,N-dimethylformamide (DMF) into a small beaker. Then weigh 0.005 mol of ammonium molybdate and 0.025 mol of thiourea into the DMF and stir until dissolved.

[0055] S102. Add 8.0 g of anhydrous ethanol and 2.0 g of polyacrylonitrile (PAN) to the above solution and stir for 1 h until PAN is dissolved.

[0056] S103. Weigh 0.005 mol of SeO2 into 2.5 mL of 80% ethylenediamine, stir for 1.5 h, and then add dropwise to the above mixed solution. The molar ratio of the Mo source, S source, and Se source in the mixed solution is 1:5:1, the mass fraction of the polymer is 10%, and the mixed solution is stirred for a total of 18 h at 1000 rpm.

[0057] S2: Preparation of a prefabricated membrane containing Mo, S and Se sources by electrospinning: S201: After the spinning solution is allowed to stand until it is uniform and free of bubbles, the mixed solution is injected into a 20 ml plastic syringe equipped with a 20-gauge needle. The needle of the syringe is connected to a 20 kV high-voltage power supply. The distance between the needle and the collecting metal plate is 12 cm. The spinning solution flow rate is set to 1.5 ml h -1 , the spinning time was 5 h, and the fiber membrane was collected by tin foil; S202: After spinning, the fiber membrane is placed in an oven at 50°C and dried for 12 hours to obtain a uniformly dried prefabricated membrane; S3: calcining the prefabricated membrane to prepare MoS (2-x) Se x @NC Composites: S301: Remove the film from the tin foil surface with tweezers and place it in a clean porcelain boat, ensuring that the film is fluffy and distributed. Then place the porcelain boat in a vacuum tube furnace filled with nitrogen. Use gradient insulation. The first stage is set at a heating rate of 10 ℃ / min, a reaction temperature of 500 ℃, and a holding time of 90 min. This allows the Mo source and the S source to react fully to form MoS2 and complete the initial carbonization of the polymer. The second stage is set at a heating rate of 10 ℃ / min, a reaction temperature of 900 ℃, and a holding time of 40 min. This allows the Se source to partially replace the S atoms in MoS2, while increasing the degree of carbonization of the polymer to form MoS (2-x) Se x @C composite materials.

[0058] S302: After the reaction is completed in a nitrogen atmosphere, the sample is collected to obtain N-doped C-coated MoS (2-x) Se x (MoS (2-x) Se x @NC) composite positive electrode materials.

[0059] Example 6 MoS for positive electrode of aqueous zinc ion battery (2-x) Se x @NC material and preparation method thereof, comprising the following steps: S1. Prepare electrospinning solution containing Mo source, S source and Se source: S101. Pour 2 mL of N,N-dimethylformamide (DMF) into a small beaker. Then weigh 0.03 mol of ammonium tetrathiomolybdate into the DMF and stir until dissolved.

[0060] S102. Add 10.0 g of anhydrous ethanol and 3.0 g of polyvinylidene fluoride (PVDF) to the above solution and stir for 2 h until the PVDF is dissolved.

[0061] S103. Weigh 0.03 mol of Se powder and add it to 2.0 mL of 80% hydrazine hydrate. Stir for 2 h, then add it dropwise to the above mixed solution. The molar ratio of Mo source, S source, and Se source in the mixed solution is 1:4:1, the mass fraction of the polymer is 11%, and the mixed solution is stirred for a total of 24 h at 800 rpm.

[0062] S2: Preparation of a prefabricated membrane containing Mo, S and Se sources by electrospinning: S201: After the spinning solution is allowed to stand until it is uniform and free of bubbles, the mixed solution is injected into a 20 ml plastic syringe equipped with an 18-gauge needle. The needle of the syringe is connected to a 30 kV high-voltage power supply. The distance between the needle and the collecting metal plate is 12 cm. The spinning solution flow rate is set to 2.0 ml·h -1 , the spinning time was 7 h, and the fiber membrane was collected by tin foil; S202: After spinning, the fiber membrane is placed in an oven at 60°C and dried for 12 hours to obtain a uniformly dried prefabricated membrane; S3: calcining the prefabricated membrane to prepare MoS (2-x) Se x @NC Composites: S301: Remove the film from the tin foil surface with tweezers and place it in a clean porcelain boat, ensuring that the film is fluffy and distributed. Then place the porcelain boat in a vacuum tube furnace filled with nitrogen. Use gradient insulation. The first stage is set at a heating rate of 8 ℃ / min, a reaction temperature of 400 ℃, and a holding time of 120 min. This allows the Mo source and the S source to react fully to form MoS2 and complete the initial carbonization of the polymer. The second stage is set at a heating rate of 5 ℃ / min, a reaction temperature of 800 ℃, and a holding time of 60 min. This allows the Se source to partially replace the S atoms in MoS2, while increasing the degree of carbonization of the polymer to form MoS (2-x) Se x @C composite materials.

[0063] S302: After the reaction is completed in a nitrogen atmosphere, the sample is collected to obtain N-doped C-coated MoS (2-x) Se x (MoS (2-x) Se x @NC) composite positive electrode materials.

[0064] Example 7 Except that the amount of the substance in ammonium tetrathiomolybdate in S101 is 0.001, the remaining steps are the same as those in Example 3.

[0065] Example 8 Except that the sulfur source in S101 is thiourea, thioacetamide, and sulfur powder (molar ratio of 1:1:1), the remaining steps are the same as those in Example 5.

[0066] Comparative Example 1 S1. Prepare electrospinning solution containing both Mo source and S source: S101. Pour 2 mL of N,N-dimethylformamide (DMF) into a small beaker. Then weigh 0.0015 mol of ammonium tetrathiomolybdate into the DMF and stir until dissolved.

[0067] S102. Add 4.0 g of anhydrous ethanol and 1.0 g of polyvinylpyrrolidone (PVP) to the above solution and stir for 1.5 h until the PVP dissolves. The mass fraction of the polymer in the mixed solution is 13.5%.

[0068] S2: Preparation of a prefabricated membrane containing both Mo and S sources by electrospinning: S201: After the spinning solution is allowed to stand until it is uniform and free of bubbles, the mixed solution is injected into a 5 ml plastic syringe equipped with a 24-gauge needle. The needle of the syringe is connected to a 30 kV high-voltage power supply. The distance between the needle and the collecting metal plate is 8 cm. The spinning solution flow rate is set to 0.8 ml h -1 , the spinning time was 4 h, and the fiber membrane was collected by tin foil; S202: After spinning, the fiber membrane is placed in an oven at 50°C and dried for 10 hours to obtain a uniformly dried prefabricated membrane; S3: Calcination treatment of the prefabricated membrane to prepare MoS2@NC composite material: S301: Remove the film from the tinfoil surface with tweezers and place it in a clean porcelain boat, ensuring the film is fluffy and distributed. The boat is then placed in a vacuum tube furnace filled with nitrogen. A gradient heat treatment is employed: the first stage is set at a heating rate of 5°C / min, a reaction temperature of 300°C, and a holding time of 120 minutes. This allows the Mo and S sources to react preferentially and fully to form MoS2 and complete the initial carbonization of the polymer. The second stage is set at a heating rate of 5°C / min, a reaction temperature of 600°C, and a holding time of 30 minutes to further carbonize the polymer and form the MoS2@NC composite.

[0069] S302: After the reaction is completed in a nitrogen atmosphere, the sample is collected to obtain an N-doped C-coated MoS2 (MoS2@NC) composite cathode material.

[0070] MoS2@NC was observed using a field emission scanning electron microscope (S4800). Figure 6 , which shows a uniform one-dimensional nanowire structure with a diameter of about 2 μm. The interlayer spacing of MoS2@NC prepared without the introduction of Se source is larger than that of MoS(2-x) Se x @NC is small and has no defective structure, which makes the migration resistance of zinc ions inside the electrode material larger, resulting in poor electrochemical performance. MoS2@NC and MoS (2-x) Se x @NC material performance comparison Figure 5 .

[0071] Comparative Example 2 MoS was prepared by direct calcination without electrospinning. (2-x) Se x @NC material, including the following steps: S1. Prepare a mixed solution containing Mo source, S source and Se source: S101. Pour 2 mL of N,N-dimethylformamide (DMF) into a small beaker. Then weigh 0.0015 mol of ammonium tetrathiomolybdate into the DMF and stir until dissolved.

[0072] S102. Add 2.0 g of anhydrous ethanol and 1.0 g of polyvinylpyrrolidone (PVP) to the above solution and stir for 1.5 h until the PVP is dissolved.

[0073] S103. Weigh 0.0015 mol of Se powder and add it to 1.5 mL of 80% hydrazine hydrate. Stir for 1.5 hours, then add it dropwise to the mixed solution. The molar ratio of the Mo source, S source, and Se source in the mixed solution is 1:4:1, and the mass fraction of the polymer is 14.3%. Stir the mixed solution for a total of 8 hours at 500 rpm.

[0074] S2: The mixed solution is dried in an oven and then calcined to prepare MoS (2-x) Se x @NC Composites: S201: The mixed solution was dried in an oven at 50°C to obtain a powder. The powder was spread flat on a porcelain boat, and the porcelain boat was placed in a vacuum tube furnace filled with nitrogen. A gradient heat preservation was used. The first stage was set at a heating rate of 5°C / min, a reaction temperature of 300°C, and a holding time of 120 min. This allowed the Mo source and the S source to react fully to form MoS2 and complete the initial carbonization of the polymer. The second stage was set at a heating rate of 5°C / min, a reaction temperature of 600°C, and a holding time of 30 min. This allowed the Se source to partially replace the S atoms in MoS2, while increasing the degree of carbonization of the polymer to form MoS2. (2-x) Se x @C composite materials.

[0075] S202: After the reaction is completed in a nitrogen atmosphere, the sample is collected to obtain N-doped C-coated MoS (2-x)Se x (MoS (2-x) Se x @NC) composite positive electrode materials.

[0076] MoS was observed using a field emission scanning electron microscope (S4800). (2-x) Se x @NC, such as Figure 7 The material exhibited a phenomenon of particle agglomeration to form large clusters, whereas the electrospinning process in Example 3 uniformly dispersed the particles within the one-dimensional carbon fibers. In Comparative Example 2, particle agglomeration significantly reduced the material's total specific surface area, which directly affected the contact interface between the material and the electrolyte, reducing the number of effective active sites available for zinc ion reaction, resulting in a lower zinc ion storage capacity.

[0077] Comparative Example 3 Comparative Example of MoS Preparation without Carbonization and Nitrogen Doping (2-x) Se x Materials, including the following steps: S1. Prepare electrospinning solution containing Mo source, S source and Se source: S101. Pour 2 mL of N,N-dimethylformamide (DMF) into a small beaker. Then weigh 0.0015 mol of ammonium tetrathiomolybdate into the DMF and stir until dissolved.

[0078] S102. Add 2.0 g of anhydrous ethanol and 1.0 g of polyvinylpyrrolidone (PVP) to the above solution and stir for 1.5 h until the PVP is dissolved.

[0079] S103. Weigh 0.0015 mol of Se powder and add it to 1.5 mL of 80% hydrazine hydrate. Stir for 1.5 hours, then add it dropwise to the mixed solution. The molar ratio of the Mo source, S source, and Se source in the mixed solution is 1:4:1, and the mass fraction of the polymer is 14.3%. Stir the mixed solution for a total of 8 hours at 500 rpm.

[0080] S2: Preparation of a prefabricated membrane containing Mo, S and Se sources by electrospinning: S201: After the spinning solution is allowed to stand until it is uniform and free of bubbles, the mixed solution is injected into a 5 ml plastic syringe equipped with a 24-gauge needle. The needle of the syringe is connected to a 40 kV high-voltage power supply. The distance between the needle and the collecting metal plate is 8 cm. The spinning solution flow rate is set to 0.8 ml·h -1 , the spinning time was 4 h, and the fiber membrane was collected by tin foil; S202: After spinning, the fiber membrane is placed in an oven at 50°C for 10 hours to obtain a uniformly dried prefabricated membrane; the membrane only contains Mo source, S source, Se source, C source and N source, and is not carbonized or doped.

[0081] The fiber membrane prepared in Comparative Example 3 contains only Mo source, S source, Se source, C source and N source in ionic form. These substances have no active sites as electrode materials and cannot react with zinc ions to achieve the purpose of energy storage.

[0082] Example 9 The prepared MoS (2-x) Se x The @NC material, conductive agent (super P, acetylene black), and binder (polyvinylidene fluoride) were mixed in a mortar at a mass ratio of 7:2:1 or 8:1:1. An appropriate amount of N-methylpyrrolidine was added and ground into a uniform paste. Using an ethanol-cleaned stainless steel mesh as the current collector, the slurry was evenly coated on the mesh. After drying, the mesh was cut into circular positive electrode sheets with a diameter of 10 mm. CR2032 button cells were assembled using 2 M Zn(CF3SO3)2 or 2 M ZnSO4 as the electrolyte, Zn foil as the negative electrode, and glass fiber as the separator.

[0083] Each embodiment in this specification is described in a related manner. Similar parts between the various embodiments can be referred to in conjunction with each other. Each embodiment focuses on the differences between the other embodiments. In particular, the system embodiment is generally similar to the method embodiment, so the description is relatively simple. For related parts, refer to the description of the method embodiment.

[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention are included in the scope of protection of the present invention.

Claims

1. A method for preparing a positive electrode material for an aqueous zinc ion battery, characterized in that: The following steps are involved: An electrospinning solution containing a molybdenum source, a sulfur source and a selenium source is prepared, and a composite prefabricated membrane containing three element precursors of molybdenum, sulfur and selenium is prepared by electrospinning; The composite prefabricated membrane is calcined to obtain MoS (2-x) Se x @NC Composites.

2. A method for preparing an aqueous zinc ion battery cathode material according to claim 1, characterized in that: The electrospinning solution preparation process comprising a molybdenum source, a sulfur source and a selenium source is as follows: A molybdenum source and a sulfur source are added as solutes to N,N-dimethylformamide and stirred until dissolved; then anhydrous ethanol and a polymer are added and stirred until the polymer is dissolved to obtain a DMF mixed solution; then a selenium source is added to a reducing solvent, stirred for 0.5 to 2 hours, and then added dropwise to the DMF mixed solution and stirred at a speed of 300 to 1000 r for 4 to 24 hours to obtain an electrospinning solution containing the molybdenum source, the sulfur source and the selenium source.

3. A method for preparing an aqueous zinc ion battery cathode material according to claim 2, characterized in that: The molybdenum source includes one or a mixture of ammonium molybdate and ammonium tetrathiomolybdate; the sulfur source includes a mixture of one or more of thioacetamide, thiourea, and sulfur powder; the selenium source includes one of Se powder and SeO2; the polymer is one of polyvinyl pyrrolidone and polyacrylonitrile; when ammonium tetrathiomolybdate is used as the molybdenum source, the sulfur source is not introduced.

4. A method for preparing an aqueous zinc ion battery positive electrode material according to claim 2, characterized in that: The reducing solvent comprises one of hydrazine hydrate and ethylenediamine, and the mass fraction of the reducing solvent is 50% to 80%.

5. A method for preparing an aqueous zinc ion battery positive electrode material according to claim 2, characterized in that: In the process of adding the molybdenum source and the sulfur source as solutes into N,N-dimethylformamide, the amount and volume ratio of the solute to the solvent is 0.25 to 30 mol / L; In the process of adding anhydrous ethanol and polymer and stirring until the polymer is dissolved, the mass volume ratio of anhydrous ethanol to the above-mentioned N,N-dimethylformamide is 1.0-2.5 g / mL, and the mass volume ratio of polymer to N,N-dimethylformamide is 0.5-0.75 g / mL; In the process of adding the selenium source into the reducing solvent and stirring, the amount and volume ratio of the selenium source to the reducing solvent is 0.33~30 mol / L.

6. A method for preparing an aqueous zinc ion battery positive electrode material according to claim 2, characterized in that: In the electrospinning solution containing a molybdenum source, a sulfur source and a selenium source at the same time, the molar ratio of the molybdenum source, the sulfur source and the selenium source is 1:2-5:1, the mass fraction of the polymer is 10%-15%, and the molecular weight of the polymer is ≥1300000.

7. A method for preparing an aqueous zinc ion battery positive electrode material according to claim 1, characterized in that: The specific process of electrospinning is as follows: S201. The electrospinning solution containing the molybdenum source, the sulfur source and the selenium source is allowed to stand until the spinning solution is uniform and free of bubbles, and then injected into a 5-20 ml syringe equipped with an 18-25 gauge needle. The needle of the syringe is connected to a 20-40 KV high voltage power supply. The distance between the needle and the collecting metal plate is 8-12 cm. The spinning solution flow rate is set to 0.5-2.0 ml·h -1 , the spinning time was 4-8 h, and the fiber membrane was collected by tin foil; S202. After spinning, the fiber membrane is placed in an oven at a temperature of 40-60°C for drying for 8-12 hours to obtain a uniformly dried composite prefabricated membrane containing the three element precursors of molybdenum, sulfur and selenium.

8. The method for preparing a positive electrode material for an aqueous zinc ion battery according to claim 1, wherein: The specific process of calcining the composite prefabricated film is as follows: placing the composite prefabricated film containing the three element precursors of molybdenum, sulfur and selenium into a clean porcelain boat to ensure that the film is fluffy and distributed, and then placing the porcelain boat in a vacuum tube furnace filled with nitrogen; using gradient insulation, setting the heating rate of the first stage to 3-10 °C / min, the reaction temperature to 300-500 °C, and the insulation time to 60-120 min; setting the heating rate of the second stage to 3-10 °C / min, the reaction temperature to 600-900 °C, and the insulation time to 30-60 min, to form MoS (2-x) Se x @NC Composites.

9. A positive electrode material for an aqueous zinc ion battery prepared by a method for preparing a positive electrode material for an aqueous zinc ion battery as claimed in any one of claims 1 to 8.

10. Use of a positive electrode material for aqueous zinc ion batteries according to claim 9, wherein the positive electrode material is used in aqueous zinc ion batteries.

Citation Information

Cited By

  • Manganese sulfide-based sodium storage electrode material, preparation method and application

    CN121085321A